The Trans-Indianica maritime networks and its impacts on Malay civilivation: revisiting the history of Kedah kingdom - Fathil, Fauziah; Wan Fazli, Wan Norrizati; Mansor Majdin, Mohamad Firdaus; H. Osman, Rahmah Ahmad; Yaapar, Md. Salleh; Alzeheimi, Saleh (International Journal of Early Childhood Special Education, 2022)
The rise of civilizations is not possible without human connectivity. Making contacts with people of other societies via commerce and trade, or cultural and diplomatic relations with other countries are foundations of the birth of kingdoms and human civilizations. This paper seeks to revisit the history of Kedah Kingdom by looking at the changes experienced by Kedah and its people resulting from the contacts with outsiders via the trans-Indianica maritime networks. Using mainly content analysis and qualitative research approach, the findings of this study will illustrate the various socio-cultural, economic and political impacts on Kedah resulting from the contacts, some of which are temporary while some are long-lasting. In doing so, this paper will highlight whenever necessary, the conducive factors that made it possible for the changes to take place and they include the geo-political state of Kedah as well as socio-economic landscape of the Kingdom which presently is the longest surviving Malay kingdom in the Peninsula since ancient times.